Shakespeare and the truth-teller : confronting the cynic ideal - Hershinow, David (Edinburgh critical studies in Shakespeare and philosophy., 2019)
Highlighting the necessity of literary thinking to political philosophy, this book explores Shakespeare's responses to sixteenth-century debates over the revolutionary potential of Cynic critical activity.